2016
DOI: 10.1038/nature18284
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum-catalysed synthesis of microporous 3D graphene-like carbons in a zeolite template

Abstract: Three-dimensional graphene architectures with periodic nanopores—reminiscent of zeolite frameworks—are of topical interest because of the possibility of combining the characteristics of graphene with a three-dimensional porous structure. Lately, the synthesis of such carbons has been approached by using zeolites as templates and small hydrocarbon molecules that can enter the narrow pore apertures. However, pyrolytic carbonization of the hydrocarbons (a necessary step in generating pure carbon) requires high te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
231
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(245 citation statements)
references
References 37 publications
9
231
0
Order By: Relevance
“…With the aid of 13 CNMR spectroscopy,w e found that surface carbon is mainly of ap olyaromatic nature as characterized by ab road peak centered at 128 ppm (Figure 3a). [17] Furthermore,w hile the amount of carbon deposited on the catalysts during the induction period is similar, the C/Mo ratio varies from about 12 for 1%Mo to about 4f or 5%Mo, suggesting that confined carbon is not exclusively bound to Mo-species (Supporting Information, Figure S13, Table S2). We also found that the H/C ratio of surface carbon species is about 0.5, and that it remains constant during the reaction (Supporting Information, Figure S14).…”
Section: Chemistryt He Main Question Remains Unanswered Namelymentioning
confidence: 99%
“…With the aid of 13 CNMR spectroscopy,w e found that surface carbon is mainly of ap olyaromatic nature as characterized by ab road peak centered at 128 ppm (Figure 3a). [17] Furthermore,w hile the amount of carbon deposited on the catalysts during the induction period is similar, the C/Mo ratio varies from about 12 for 1%Mo to about 4f or 5%Mo, suggesting that confined carbon is not exclusively bound to Mo-species (Supporting Information, Figure S13, Table S2). We also found that the H/C ratio of surface carbon species is about 0.5, and that it remains constant during the reaction (Supporting Information, Figure S14).…”
Section: Chemistryt He Main Question Remains Unanswered Namelymentioning
confidence: 99%
“…5 Moreover, these materials possess high intrinsic electrical conductivity that facilitates the electron transfer processes for hydrazine oxidation along with high surface area. 6 These striking properties have led to the use of carbon-based materials for various fuel-cell technologies, including hydrazine fuel cells. For instance, Li et al 7 showed that a complex of graphene and carbon nanotubes can be effectively utilized for the oxygen reduction reaction on the anode side of the fuel cell.…”
Section: Introductionmentioning
confidence: 99%
“…4,20 More recently, nano-porous zeolites decorated with Lanthanum have been used as a template to create carbon frameworks, albeit not fully graphitised. 7 Further, computational modelling has recently highlighted the potentially exceptional properties of periodic gyroid graphene structures. 13 A well-known challenge in particular for pure metal templates is their high self-diffusivity, 21 which means that metal templates with sub-100 nm unit cell sizes are prone to sintering, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature highlights the promise of such porous, foam-like materials, in particular those derived from graphene, in applications ranging from (opto)electronics, 1,2 artificial skin, 3 electrochemistry, [4][5][6] and catalysis 7 to thermal management, 8 self-cleaning, 9 sorption and filtration, 10 sensors, 11 bio-medical 12 and mechanical metamaterials. 13,14 Among the various synthetic strategies and 3D assembly approaches, 15 chemical vapour deposition (CVD) has emerged as the most viable route not only to grow highly crystalline 2D material films but also to directly grow covalently bonded, continuous 3D networks of these 2D materials.…”
Section: Introductionmentioning
confidence: 99%